2015
DOI: 10.1103/physrevlett.114.220402
|View full text |Cite
|
Sign up to set email alerts
|

Simple Explanation of the Quantum Limits of Genuinen-Body Nonlocality

Abstract: Quantum n-body correlations cannot be explained with (n-1)-body nonlocality. However, this genuine n-body nonlocality cannot surpass certain bounds. Here we address the problem of identifying the principles responsible for these bounds. We show that, for any n≥2, the exclusivity principle, as derived from axioms about sharp measurements, and a technical assumption give the exact bounds predicted by quantum theory. This provides a unified explanation of the bounds of single-body contextuality and n-body nonloca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…This difference stimulated the search for principles singling out Tsirelson's bound as part of the effort for understanding quantum theory from fundamental principles. So far, the following principles have been identified that enforce Tsirelson's bound: information causality [5], macroscopic locality [6], and exclusivity [7]. Other principles, such as non-signaling [4] and nontriviality of communication complexity [8,9], allow for higher values.…”
mentioning
confidence: 99%
“…This difference stimulated the search for principles singling out Tsirelson's bound as part of the effort for understanding quantum theory from fundamental principles. So far, the following principles have been identified that enforce Tsirelson's bound: information causality [5], macroscopic locality [6], and exclusivity [7]. Other principles, such as non-signaling [4] and nontriviality of communication complexity [8,9], allow for higher values.…”
mentioning
confidence: 99%
“…No physical principle has yet been able to explain the quantum maxima for S(C 7 ) and S(C 7 ). However, the exclusivity principle [25][26][27][28] singles out the quantum maxima of the following NC inequality:…”
Section: Why These Maxima?mentioning
confidence: 99%
“…Each of these alternatives identifies a particular feature of QT that we do not fully understand and, as a matter of fact, may or may not be satisfied by nature. For example, we still do not know which principle singles out the set of correlations in QT [5]. In contrast, the set of almost quantum correlations satisfies a list of reasonable principles and is simple to characterize [2].…”
Section: Introductionmentioning
confidence: 98%